Infectious bursal disease virus assembly causes endoplasmic reticulum stress and lipid droplet accumulation - Frontini-López, Yesica R.; Rivera, Lautaro; Pocognoni, Cristian A.; Roldán, Julieta Suyai; Colombo, Maria Isabel; Uhart, Marina; Delgui, Laura Ruth (MDPI, 2023)
Gumboro illness is caused by the highly contagious immunosuppressive infectious bursal disease virus (IBDV), which affects the poultry industry globally. We have previously shown that IBDV hijacks the endocytic pathway to construct viral replication complexes on endosomes linked to the Golgi complex (GC). Then, analyzing crucial proteins involved in the secretory pathway, we showed the essential requirement of Rab1b, the Rab1b downstream effector Golgi-specific BFA resistance factor 1 (GBF1), and its substrate, the small GTPase ADP-ribosylation factor 1 (ARF1), for IBDV replication. In the current work, we focused on elucidating the IBDV assembly sites. We show that viral assembly occurs within single-membrane compartments closely associated with endoplasmic reticulum (ER) membranes, though we failed to elucidate the exact nature of the virus-wrapping membranes. Additionally, we show that IBDV infection promotes the stress of the ER, characterized by an accumulation of the chaperone binding protein (BiP) and lipid droplets (LDs) in the host cells. Overall, our results represent further original data showing the interplay between IBDV and the secretory pathway, making a substantial contribution to the field of birnaviruses–host cell interactions.